KEANEKARAGAMAN SPESIES KUPU-KUPU (LEPIDOPTERA:RHOPALOCERA) DI SAVANA PRINGTALI RESORT BANDEALIT TAMAN NASIONAL MERU BETIRI - Rendy Setiawan; Arif Mohammad Siddiq; Sudarmadji sudarmadji; Nindy Agusti Wulansari (Universitas Medan Area, 2019)
Butterfly is the insect that the existence is determined by the ability of their distribution and adaptation towards the environmental factor. The decrease of the plant species diversity in a habitat will affect the diversity of the butterfly species. One of the buterflies habitat which experinces the degradation of species diversity is Resort Bandealit which some parts of the region are designated as the habitat of Invasive plants. The aim of this study is to know the composition and diversity of butterfly species in the pringtali Savannah Resort Bandealit Meru Betiri national park. The method used in the data collection is the road sampling method. The road sampling method is done by walking and counting spesimen which were collect by active collection. Exploration is carried out by walking along the five cruise lines with a length of each path is 100 m in Savana Pringtali Meru Betiri National Park. The composition and diversity species of butterfly is a 11 species represented from 3 family and 10 genus. The four most common species of butterflies found in the study area are Jamides pura, Ypthima Philomela, Leptosia nina, and Eurema hecabe.